2010
DOI: 10.1523/jneurosci.2239-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

A Temporal Hierarchy for Conspecific Vocalization Discrimination in Humans

Abstract: The ability to discriminate conspecific vocalizations is observed across species and early during development. However, its neurophysiologic mechanism remains controversial, particularly regarding whether it involves specialized processes with dedicated neural machinery. We identified spatiotemporal brain mechanisms for conspecific vocalization discrimination in humans by applying electrical neuroimaging analyses to auditory evoked potentials (AEPs) in response to acoustically and psychophysically controlled n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
89
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 51 publications
19
89
2
1
Order By: Relevance
“…No previous research to our knowledge has examined judgments of whether stimuli were produced by human or nonhuman animals, but neuroimaging work has examined cerebral responses to nonhuman animal vocalizations relative to a variety of other stimuli including human voices (e.g., Lewis, Brefczynski, Phinney, Janik, & DeYoe, 2005;Altmann, Doehrmann, & Kaiser, 2007;Belin et al, 2008). De Lucia, Clarke, andMurray (2010) found that human and nonhuman animal vocalizations elicited early responses in statistically indistinguishable brain networks.…”
Section: Methodsmentioning
confidence: 99%
“…No previous research to our knowledge has examined judgments of whether stimuli were produced by human or nonhuman animals, but neuroimaging work has examined cerebral responses to nonhuman animal vocalizations relative to a variety of other stimuli including human voices (e.g., Lewis, Brefczynski, Phinney, Janik, & DeYoe, 2005;Altmann, Doehrmann, & Kaiser, 2007;Belin et al, 2008). De Lucia, Clarke, andMurray (2010) found that human and nonhuman animal vocalizations elicited early responses in statistically indistinguishable brain networks.…”
Section: Methodsmentioning
confidence: 99%
“…The solution space included 3005 nodes, selected from a 6 Â 6 Â 6 mm grid equally distributed within the gray matter of the averaged brain of the Montreal Neurological Institute (MNI; courtesy of Grave de Peralta Menendez and Gonzalez Andino, University Hospital of Geneva, Geneva, Switzerland). In order to control for multiple comparisons, only solutions with a minimal cluster size of 15 consecutive points (k E ) were retained (see also De Lucia, Clarke, & Murray, 2010;Knebel & Murray, 2012).…”
Section: Electrical Source Estimationsmentioning
confidence: 99%
“…The optimal number of temporally stable ERP clusters (i.e., the minimal number of maps that accounts for the greatest variance of the dataset) was determined using a modified Krzanowski-Lai criterion (Murray et al, 2008). The clustering makes no assumption on the orthogonality of the derived template maps (Pourtois et al, 2008;De Lucia et al, 2010). Template maps identified in the group-average ERP were then submitted to a fitting procedure wherein each time point of each single-subject ERP is labeled according to the template map with which it best correlated spatially (Murray et al, 2008) so as to statistically test the presence of each map in the moment-by-moment scalp topography of the ERP and the differences in such across conditions.…”
Section: Eeg Acquisition and Analysesmentioning
confidence: 99%